Anda di halaman 1dari 11

G (X) = Po + (1 - Po) F (X)

( )

=

2  µ  1 1  −  ⋅ exp  −   
2
µ
1
1
 −
exp
2
π σ
2
σ

µ σ α

µ σ µ σ

( ) =

(

)

1 = ∫ σ 2 π
1
=
σ
2
π

(

2

)

µ

2

2

σ

= −

1

α

µ σ

1  1  ( ) 2 − ∞ < < +∞ = ⋅ exp −
1
1
( )
2
− ∞ < < +∞
=
exp
2
π
2

( ) 2 ∞ 1  [ ln − − µ ]  ( ) =
(
)
2
1
[
ln
µ
]
( ) =
exp −
Γ
(
α
α
)
1
=
(
2
)
σ
2
π
2
σ
0
µ
σ
α
ˆ
2
3
=
( )
+
+
+
...
  1 +
ˆ
Γ
(
α
ˆ
)
α
α
ˆ + 1
(
α
ˆ +
1
)(
α
ˆ
+ 2
)
(
α
ˆ +
1
)(
α
ˆ
+
2
)(
α
ˆ
+ 3
)
( )
ˆ
= ⋅
β
[
(
)
]
2
1
ln
µ
(
)
= ∫
exp −
=
1
α
(
)
2
σ
2
π
2
σ
α β
2
12
α
6
α −
1
=
0
(
> 0 )
1
4
ˆ
α α > 0 β β > 0
α
=
1
+
1
+
4
3
1
( )
α
− 1
β
=
α
β
Γ
(
α
)
ˆ
β
=
α
ˆ
( ) = 0 ≤ 0
( ≤ )
α
β
Γ (α )
= ln −
1
=
= 1
1
=
ln
(
)
= 1

( )

=

λ

λ

> 0

( ) = 0 0

()

=

(

0

)

=

(

)

=

1

λ

0

=

1

α

λ

( )

=

γ

   

α

 

γ

1

α

β

β

β

exp

−   

 

 

 

γ

α

( ) = 0 α

()

=

(

0

)

=

( )

=

0

1

exp

− 

α

β

γ       
γ
 
 

=

1

α

γ β β γ β

= 1

ˆ

γ

ln(

)

ln(

)

= 1

1

= 1

ˆ

γ

= 0

ˆ

β

=

1

(

ln

ˆ

γ

1

)

ˆ

γ

χ

χ

χ

2

=

= 1

(

)

2

α = 0,05

α β β

α β